2012
DOI: 10.1155/2012/608534
|View full text |Cite
|
Sign up to set email alerts
|

The Neurological Complications of Nutritional Deficiency following Bariatric Surgery

Abstract: Neurologic complications of bariatric surgery have become increasingly recognized with the rising numbers of procedures and the increasing prevalence of obesity in the US. Deficits are most commonly seen with thiamine, vitamin B12, folate, vitamin D, vitamin E, and copper deficiencies. The neurological findings observed with these nutritional deficiencies are variable and include encephalopathy, optic neuropathy, myelopathy, polyradiculoneuropathy, and polyneuropathy. We review the neurological complications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 39 publications
1
80
0
7
Order By: Relevance
“…17 Traditionally seen in chronic alcohol abusers, WE is characterized by a subacute onset of the classic triad of ocular abnormalities, gait ataxia, and mental status changes. 18 Detailed clinical and neuropathological data from 82 autopsies and 245 patients examined over 10 years revealed that all features of the triad were recognized in only one-third of patients; in most, only 1 or 2 elements of the clinical triad were apparent. 19 Mental status changes include inability to concentrate, indifference, spatial disorientation, delirium, and psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Traditionally seen in chronic alcohol abusers, WE is characterized by a subacute onset of the classic triad of ocular abnormalities, gait ataxia, and mental status changes. 18 Detailed clinical and neuropathological data from 82 autopsies and 245 patients examined over 10 years revealed that all features of the triad were recognized in only one-third of patients; in most, only 1 or 2 elements of the clinical triad were apparent. 19 Mental status changes include inability to concentrate, indifference, spatial disorientation, delirium, and psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…The axonal neuropathy is the most common type of PN and it may be recovered after vitamin supplementation [89,90]. On the other hand, folate deficiency has been also associated with PN in patients with IBD [91].…”
Section: Other Vitamin B Group Deficienciesmentioning
confidence: 99%
“…Severe vitamin E deficiency can produce a progressive sensory axonopathy, especially involving large fibers [89,94].…”
Section: Vitamin E Deficiencymentioning
confidence: 99%
“…The prevalence of decreased vitamin levels and ferritin levels in the first 3 years after bariatric surgery points in this direction ( Table 1). Supplementation of vitamins and micronutrients is routine, especially after sleeve gastrectomy and gastric bypass procedures, to avoid rare irreversible side effects such as polyneuropathy associated with vitamin B12 deficiency (33). Finally, refeeding syndrome with Wernicke's encephalopathy, due to thiamine deficiency has been reported after obesity surgery (34), although it is exceptionally rare (33).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of vitamins and micronutrients is routine, especially after sleeve gastrectomy and gastric bypass procedures, to avoid rare irreversible side effects such as polyneuropathy associated with vitamin B12 deficiency (33). Finally, refeeding syndrome with Wernicke's encephalopathy, due to thiamine deficiency has been reported after obesity surgery (34), although it is exceptionally rare (33). Refeeding syndrome is an important complication of parenteral or enteral resumption of nutrition after malnourishment and reflects the change from catabolic to anabolic metabolism.…”
Section: Introductionmentioning
confidence: 99%